Exchange rate pass-through, markups, and inventories - Adam Copeland; James A. Kahn (Federal Reserve Bank of New York, 2012)
A large body of research has established that exporters do not fully adjust their prices across countries in response to exchange rate movements, but instead allow their markups to vary. But while markups are difficult to observe directly, we show in this paper that inventory-sales ratios provide an observable counterpart. We then find evidence that inventory-sales ratios of imported vehicles respond to exchange rate movements to a degree consistent with pass-through on the order of 50 to 75 percent, on the high end of the range found in the literature.
Keywords: F12; L11; L62; 330; exchange rate; pass-through; inventories; motor vehicles